CdSe/ZnS quantum dots as sensors for the local refractive index. Issue 4 (11th January 2016) - Aubret, Antoine; Pillonnet, Anne; Houel, Julien; Dujardin, Christophe; Kulzer, Florian
Abstract : An effective medium approach was used to quantify the sensitivity of individual fluorescent nanocrystals to changes in their dielectric environment. Abstract : We explore the potential of CdSe/ZnS colloidal quantum dots (QDs) as probes for their immediate dielectric environment, based on the influence of the local refractive index on the fluorescence dynamics of these nanoemitters. We first compare ensembles of quantum dots in homogeneous solutions with single quantum dots dispersed on various dielectric substrates, which allows us to test the viability of a conceptual framework based on a hard-sphere region-of-influence and the Bruggeman effective-medium approach. We find that all our measurements can be integrated into a coherent description, provided that the conceptualized point-dipole emitter is positioned at a distance from the substrate that corresponds to the geometry of the QD. Three theoretical models for the evolution of the fluorescence decay rate as a function of the local refractive index are compared, showing that the classical Lorentz approach (virtual cavity) is the most appropriate for describing the data. Finally, we use the observed sensitivity of the QDs to their environment to estimate the detection limit, expressed as the minimum number of traceable streptavidin molecules, of a potential QD-nanosensor based on fluorescence lifetime.